The New Grove Haydn - Larsen, Jens Peter, 1902-1988 (The new grove, 1982)
This finely judged life of Haydn by Jens Peter Larsen is balanced by an exhaustive work-list prepared by Georg Feder of the Haydn-Instiut in Cologne. The work of two of the world's foremost Haydn experts, this major biographical study brings the later scholarship to bear in discussing the composer's life and development, and carriesthe clearest, most authoritative listing of his output. This is the first full-length study of Haydnby Larsen to appear in English.